Conference on Lasers and Electro-Optics 2022
DOI: 10.1364/cleo_si.2022.sth4n.2
|View full text |Cite
|
Sign up to set email alerts
|

80-channel WDM-MDM communication link utilizing a Photonic Crystal Resonator and Inverse-Designed Mode-Division Multiplexers

Abstract: We demonstrate a 80-channel communication link with >150 Gbps error-free data transmission utilizing Photonic Crystal Resonator (PhCR) with normal dispersion as a comb source. We utilize a 4-channel inverse-designed mode-division multiplexer to increase data rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In these years, a great deal of research on MDM transmission systems has been reported in China and abroad [12,13] . In 2018, Li et al transmitted 8-WDM-channels 2-mode 20-GBaud QPSK over 100 km FMF with a transmission rate of 640 Gbit/s [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In these years, a great deal of research on MDM transmission systems has been reported in China and abroad [12,13] . In 2018, Li et al transmitted 8-WDM-channels 2-mode 20-GBaud QPSK over 100 km FMF with a transmission rate of 640 Gbit/s [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In such hybrid networks, mode-and-wavelength multiplexers and demultiplexers based on PIC are certainly inevitable. Therefore, many researches have focused on this topic, [26][27][28][29][30][31][32][33] including recent advances showing a mode-and-wavelength multiplexing of up to 32 channels 31,32 or even 80 channels. 33 However, most of the reported researches were mainly demonstrated for wavelength channels multiplexed densely within C band and the multiple band mode multiplexing remain important for further researches as it helps to combine optical bands, for example, O, S, and C bands, of densely multiplexed channels.…”
Section: Introductionmentioning
confidence: 99%